2017
DOI: 10.3892/or.2017.6155
|View full text |Cite
|
Sign up to set email alerts
|

Licochalcone A suppresses hexokinase 2-mediated tumor glycolysis in gastric cancer via downregulation of the Akt signaling pathway

Abstract: Licochalcone A (LicA) is a chalcone extracted from liquorice which has been used as a traditional Chinese medicine for many generations. Increased glucose consumption and glycolytic activity are important hallmarks of cancer cells, and hexokinase 2 (HK2) upregulation is a major contributor to the elevation of glycolysis. Recently, the antitumor activities of LicA have been reported in various cancers; however, its effect on tumor glycolysis in gastric cancer and the underlying mechanisms are completely unknown… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
43
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 44 publications
(50 citation statements)
references
References 35 publications
(42 reference statements)
3
43
0
Order By: Relevance
“…33 Early reports have indicated that licochalcone A has biological activities, including antiallergic, antiinflammation, antimycobacterial, and anticancer. [6][7][8][9][10]34,35 Our present data provide evidence that licochalcone A can induce apoptotic cell fragmentation, apoptotic body formation, and caspase activation. 36 In particular, casapse-3 has been demonstrated to be a crucial component of the mechanism responsible for the activation of apoptosis in apoptotic cells, and PARP, the cleavage of which is a hallmark of apoptosis, is a well-known downstream target of active caspase-3.…”
Section: Discussionsupporting
confidence: 63%
See 4 more Smart Citations
“…33 Early reports have indicated that licochalcone A has biological activities, including antiallergic, antiinflammation, antimycobacterial, and anticancer. [6][7][8][9][10]34,35 Our present data provide evidence that licochalcone A can induce apoptotic cell fragmentation, apoptotic body formation, and caspase activation. 36 In particular, casapse-3 has been demonstrated to be a crucial component of the mechanism responsible for the activation of apoptosis in apoptotic cells, and PARP, the cleavage of which is a hallmark of apoptosis, is a well-known downstream target of active caspase-3.…”
Section: Discussionsupporting
confidence: 63%
“…To overcome these problems, studies on combined therapy have focused on identifying phytotherapeutic agents with known action mechanisms that can augment the therapeutic index of chemotherapeutic agents, such as Lentinan combined with oxaliplatin in hepatocellular carcinoma, baicalein combined with docetaxel in thyroid cancer cells, curcumin combined with platinum in ovarian cancer cells, and Astragalus polysaccharides combined with cisplatin in nasopharyngeal carcinoma cells . Early reports have indicated that licochalcone A has biological activities, including antiallergic, anti‐inflammation, antimycobacterial, and anticancer . Our present data provide evidence that licochalcone A can induce apoptotic cell death in human HONE‐1 nasopharyngeal cancer cells.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations